Success Factors for Scaling Up the Adoption of Digital Therapeutics Towards the Realization of P5 Medicine - Prodan, Alexandra; Deimel, Lucas; Ahlqvist, Johannes; Birov, Strahil; Thiel, Rainer; Toivanen, Meeri; Kolitsi, Zoi; Kalra, Dipak (Frontiers in Medicine, 2022)
Digital therapeutics (DTx) can be a valuable contribution to the successful scale up of P5 Medicine as they offer powerful means of delivering personalization and active patient participation in disease self-management. We investigated how the approval and adoption of DTx within health systems have been approached in five selected European countries and regions, with a view to proposing success factors scaling up their adoption. Preliminary research established best candidates as Germany, UK, France, Belgium, and the Spanish Region of Catalonia. The research was informed by literature review, interviews, and a multi-stakeholder workshop. To authorize the use of digital technologies, the countries and regions passed legislation and developed policy instruments, appointed bodies to certify and formalized mechanisms for reimbursement. While DTx is not commonly used, there are digital health technologies defined that have similar requirements. Certification frameworks are usually built around the Medical Device Regulation with additional criteria. To be reimbursed, countries require manufacturers to demonstrate clinical value and cost-effectiveness. As there are currently very few DTx approved in practice, there is resistance towards clinical acceptance and organizational change. The integration and secondary use of DTx data is not encountered in daily practice. Although enablers exist, there remain technical and legal barriers. DTx strategies should be considered as an integral part of digital health strategies and legislation, and specific DTx pathways with clear and transparent assessment and guidelines that balance regulation and innovation should be defined. To help manufacturers, countries should recommend methods that are widely accepted and ensure scientific robustness to support transfer of data across countries. To facilitate rapid uptake, countries should add flexibility to the framework by allowing temporary market authorisation to enable data collection that can support the clinical and socio-economic evaluation. Certification should trigger rapid price setting and reimbursement mechanisms, and dynamic ways to adjust price and reimbursement levels in time should be established. Relevant stakeholders should be approached on the potential impacts of DTx through transparent communication and change management strategies should be considered. These findings should be validated with a wider range of stakeholders.